Learning to teach in Higher Education - Hyleen Mariaye; Majhegy Murden-Louise; Shalini Ramasawmy (SOTL in the South)
This paper reflectively analyses how informal conversational spaces can be pedagogically integrated in a formal structured learning space. We document innovative practice in faculty development by introducing elements of informal conversations, understood as serendipitous, improvised, open-ended, permissive and including an element of risk into an introductory academic development programme, namely the Post Graduate Diploma in Learning and Teaching in Higher Education. The outcome is one of enhanced opportunities for reflexivity and interdisciplinary dialogue.